PENERAPAN GOOD GOVERNANCE DALAM PELAKSANAAN PEMBANGUNAN DI NAGARI TANJUNG BONAI AUR KECAMATAN SUMPUR KUDUS KABUPATEN SIJUNJUNG - F Yasmeardi; Rini Parmila Yanti; Salma Rani Fitri (Jurnal Public Administration, Business and Rural Development Planning, 2023)
The purpose of this research is to find out how development is carried out in Nagari Tanjung Bonai Aur and to find out the application of good governance in implementing development in Nagari Tanjung Bonai Aur. Based on the results of the study it can be concluded that, 1) Good governance in Nagari tanjung bonai aur still faces several irregularities such as accountability in the form of budget realization reports not being provided to the community, community participation that is less active in development both in musrembang activities and in mutual cooperation. 2) In the implementation of development in the Nagari Tanjung Bonai Aur it can be achieved well, although there are still obstacles such as budget constraints and difficulties in land acquisition. 3). It can be said that the implementation of good governance in Nagari Tanjung Bonai Aur has been carried out well even though it has not been maximized, because in the implementation of development in Nagari Tanjung Bonai Aur the guardian of the Nagari directly involved in surveying the development needed by the people in Nagari Tanjung Bonai Aur, the survey was carried out throughout jorong in nagari tanjung bonai aur, in the implementation of development it has involved all existing elements, in the development carried out it is really what is needed by the community which has been stated in the RKP and is guided by the references to the laws that regulate it